The Injury Mechanism of Traumatic Amputation - Rankin, Iain A.; Nguyen, Thuy-Tien; McMenemy, Louise; Clasper, Jonathan C.; Masouros, Spyros D. (Frontiers in Bioengineering and Biotechnology, 2021)
Traumatic amputation has been one of the most defining injuries associated with explosive devices. An understanding of the mechanism of injury is essential in order to reduce its incidence and devastating consequences to the individual and their support network. In this study, traumatic amputation is reproduced using high-velocity environmental debris in an animal cadaveric model. The study findings are combined with previous work to describe fully the mechanism of injury as follows. The shock wave impacts with the casualty, followed by energised projectiles (environmental debris or fragmentation) carried by the blast. These cause skin and soft tissue injury, followed by skeletal trauma which compounds to produce segmental and multifragmental fractures. A critical injury point is reached, whereby the underlying integrity of both skeletal and soft tissues of the limb has been compromised. The blast wind that follows these energised projectiles completes the amputation at the level of the disruption, and traumatic amputation occurs. These findings produce a shift in the understanding of traumatic amputation due to blast from a mechanism predominately thought mediated by primary and tertiary blast, to now include secondary blast mechanisms, and inform change for mitigative strategies.